Tegalan Song: An Expression of Musical Culture Identity of the Coastal Communities of Northern Coast of Java - Andaryani, Eka Titi; Utomo, Udi (Harmonia: Journal of Arts Research and Education, 2024)
Songs, regarded as a form of musical expression, consistently mirror societal culture. This research aims to unveil and analyze the song tegalan, which serves as a portrayal of Tegal’s cultural identity. The research employs a qualitative descriptive methodology. Data collection for this study involved scrutinizing tegalan songs, particularly their lyrical content, with the purpose of comprehending the themes depicting the unique identity of the Tegal community. In addition to observation, the researcher conducted in-depth interviews with three notable tegalan song artists. A literature review was also undertaken to corroborate the research findings. The collected data was then distilled to extract information pertinent to the research theme, which was subsequently presented based on the interpretation of Tegal’s cultural identity and then conclusively analyzed. The research findings indicate that within the lyrics of tegalan songs, four cultural identities are discernible: (1) the utilization of colloquial Javanese infused with the “ngapak” dialect; (2) the characteristic of spontaneous and sincere communication reflective of the Tegal community’s culture; (3) the identity of coastal communities, which tend to exhibit straightforwardness; and (4) the diverse range of typical Tegal delicacies such as “sega ponggol”, tea with palm sugar (“teh poci gula batu”), among others. Based on these findings, it can be inferred that tegalan songs, in terms of their lyrical content, epitomize the linguistic culture of the Tegal community in both structure and communicative patterns. Moreover, in terms of messaging, these songs convey insights into the identity and distinctive attributes of the Tegal community..